Digital Adoption in Informal Micro-Property Management: A TAM–Lean–BMC Conceptual Framework and Research Agenda - Esri Hestiningtyas; Rahadi, Raden Aswin (Journal Integration of Management Studies, 2026)
This conceptual study tackles the digital-adoption gap in Jakarta's kos-kosan boarding-house rooms, where landlords managing 5–20 units still juggle paper ledgers despite near-universal smartphone and WhatsApp use. Guided by the Technology Acceptance Model (TAM), Lean Start-up logic, and the Business Model Canvas (BMC), this research develops an integrated theoretical framework that explains behavioral hesitancy, sequences low-risk Minimum Viable Product (MVP) iterations, and pinpoints the "missing-middle" niche for a boarding house management platform. The proposed framework positions TAM to surface core drivers (perceived usefulness and ease of use) recast for WhatsApp-first workflows. Lean Start-up methodology will then map these insights into quick, feedback-rich MVP cycles tuned to resource-constrained settings. BMC will situate the validated feature set in a defendable market position underserved by premium PropTech and ultra-basic bots. This conceptual foundation establishes the theoretical groundwork for future empirical phases, which will combine stakeholder interviews and platform benchmarking to diagnose pain points, quantify adoption triggers, and refine the MVP and business model through qualitative fieldwork and pilot deployments. By linking behavior, experimentation, and strategy, this study lays a theory-driven pathway toward inclusive digital transformation in informal housing in emerging economies, with empirical validation planned for subsequent research phases.